ПЕРЕДУМОВИ ТА ПОТЕНЦІАЛ ФОРМУВАННЯ СИСТЕМИ АНТИКРИЗОВОГО УПРАВЛІННЯ ЗАКЛАДУ ОСВІТИ (ІННОВАЦІЙНА ЕКОНОМІКА, 2022)
Маркова С.В., Головань О.О., Хмельницький А.А. ПЕРЕДУМОВИ ТА ПОТЕНЦІАЛ ФОРМУВАННЯ СИСТЕМИ АНТИКРИЗОВОГО УПРАВЛІННЯ ЗАКЛАДУ ОСВІТИМета. Провести внутрішній аудит розбудови середовищ закладу освіти (освітнього і виховного) за допомогою опитування усіх учасників освітнього процесу і запропонувати антикризову стратегію розвитку закладу, визначивши маркери, за якими буде оцінено результати роботи цієї системи.Методика дослідження. Задля досягнення мети використано такі методи, як: статистичний метод обробки даних, метод групування – для оцінки соціально-економічних передумов впровадження антикризового управління, дослідження стану основних показників, які формують систему діяльності закладів освіти; економіко-математичне моделювання – для розробки моделі оцінки якості освіти та основних факторів, що вагомо впливають на якість освіти (якість процесу, якість умов та якість результатів); експертний метод – для інтерпретації експертних оцінок щодо аналізу факторів та критеріїв моделі оцінки якості освіти.Результати дослідження. Проаналізовано освітнє та виховне середовища Запорізької гімназії № 17 на основі опитування усіх учасників освітнього процесу. Визначено, що наприкінці 2021-2022 н. р. показник якості освіти у гімназії є показником початкового рівня, але близьким до середнього. Виявлено, що на достатньому рівні реалізуються умови освітнього процесу, а якість процесу має початковий рівень, близький до критичного, якість результатів – також початковий рівень. Оцінку достатнього рівня мають три критерії: професійна компетентність педагогів, дотримання санітарно-гігієнічних вимог та втілення сучасних освітніх технологій. Найнижчі показники мають реалізація допрофільного навчання, курсів за вибором, факультативів та додаткової освіти, що і є причиною посередніх показників якості результатів: академічної успішності, вступ до професійних закладів освіти, результати участі в олімпіадах, творчих конкурсах.Наукова новизна результатів дослідження. У рамках комплексного внутрішнього аудиту закладу загальної середньої освіти було розроблено факторно-критеріальну модель Запорізької гімназії № 17, що дозволяє швидко заміряти стан об’єкта в будь-який момент його розвитку та становлення, виявити критичні точки та позитивні моменти.Практична значущість результатів дослідження. Розроблена факторно-критеріальна модель оцінки якості освіти є мобільною, зручною у використанні, дає можливість оцінити якість освіти в закладі за внутрішніми її факторами, виявити критичні точки і складові освітнього процесу, які стало розвиваються, і використання яких забезпечить зростання інших критеріїв. Запропоновано основні шляхи для покращення критичних значень за критеріями, показано перші кроки реалізації системи антикризового менеджменту.Ключові слова: антикризове управління, внутрішній аудит закладу освіти, факторно-критеріальна модель, антикризова стратегія розвитку. Мarkova S.V., Holovan O.O., Khmelnytskyi A.A. PREREQUISITES AND POTENTIAL FOR THE FORMATION OF A CRISIS MANAGEMENT SYSTEM OF AN EDUCATIONAL INSTITUTIONPurpose. The aim of the article is to conduct an internal audit of the development of the educational institution environment (educational and educative) by means of a survey taken by all participants of the educational process and to propose an anti-crisis strategy for the institution development, identifying markers by which the results of this system will be evaluated.Methodology of research. The following methods were used to achieve the goal: the statistical method of data processing, the grouping method to assess the social and economic prerequisites for the implementation of anti-crisis management, the study of the state of the main indicators that form the activity system of educational institutions; economic-mathematical modelling to develop a model for assessing the quality of education and the main factors that significantly affect the quality of education (quality of the process, quality of conditions and quality of results); expert method for the interpretation of expert assessments regarding the analysis of factors and criteria of the education quality assessment model.Findings. The educational and training environment of Zaporizhzhia Gymnasium No. 17 was analysed on the basis of a survey of all participants in the educational process. The designed factor-criterion model for assessing the quality of education is mobile, convenient to use, makes it possible to assess the quality of education in the institution according to its internal factors, to identify critical points and components of the educational process that have been developing, and the use of which will ensure the growth of other criteria. It was established that at the end of the 2021-2022 academic year, the indicator of the education quality in the gymnasium is at the elementary level, but close to the average. It was determined that the conditions of the educational process are implemented at the sufficient level, the quality of the process is at the elementary level, close to critical, and the quality of the results is also at the elementary level. The assessment of the sufficient level gained such three criteria: the professional competence of the teachers, compliance with sanitary and hygienic requirements, and the implementation of modern educational technologies. The implementation of pre-professional training, optional courses, electives and additional education have the lowest indicators, which is the reason for the average indicators of the quality of such results as academic success, admission to professional educational institutions, results of participation in Olympiads, creative competitions.Originality. A factor-criterion model of Zaporizhzhia Gymnasium No. 17 was developed as part of a comprehensive internal audit of the general secondary education institution, which allows to quickly measuring the condition of the object at any moment of its development and formation, to identify critical as well as positive points.Practical value. The designed factor-criterion model for assessing the quality of education is mobile, convenient to use, makes it possible to assess the quality of education in the institution according to its internal factors, to identify critical points and components of the educational process that have been developing, and the use of which will ensure the growth of other criteria. The work includes the main ways to improve the critical levels according to the criteria and demonstrates the first steps of the implementation of an anti-crisis management system.Key words: anti-crisis management, internal audit of an educational institution, factor-criterion model, anti-crisis development strategy.
Keywords: антикризове управління; внутрішній аудит закладу освіти; факторно-критеріальна модель; антикризова стратегія розвитку.